Service Oriented Architecture Adoption: A Systematic Review - Niknejad, Naghmeh; Che Hussin, Ab Razak; Prasetyo, Yuli Adam; Ghani, Imran; Fajrillah, Asti Amalia Nur (International Journal of Integrated Engineering, 2018)
Service Oriented Architecture (SOA) has appeared as an absorbing architectural approach that empowers the available systems to reveal their performance in the act of services without creating important changes to the systems. This approach, due to its flexibility of adoption, has been widely appreciated by the businesses. Though there are many studies that depict successful factors of SOA, a few minor cases of failure have also been reported in the literature. In spite of the availability of rich material on SOA, there is no systematic literature review on the influential aspect of SOA adoption factors. Thus, this paper presents a systematic literature review of existing studies (from 2009 to 2015) related to the SOA adoption and its success and failure. The central purpose of the study is to focus on the existing issues and share the findings with researchers. Moreover, the findings of this paper would help the IT experts in organizations focus on the most important factors highlighted in this study, so they could decide whether it is advisable to adopt SOA in their context or not.